2020
DOI: 10.3892/mco.2020.2132
|View full text |Cite
|
Sign up to set email alerts
|

Proximal gastrectomy with anti‑reflux anastomosis for patients with adenocarcinoma of the esophagogastric junction: The simple and safe triangle‑valve technique

Abstract: A simple and safe triangle-valve technique (TVT) was applied in proximal gastrectomy (PG) in order to prevent postoperative gastric reflux among patients with adenocarcinoma of the esophagogastric junction (AEG). The clinical outcomes were evaluated in comparison to those of canonical total gastrectomy (TG). This retrospective study of 74 AEG patients compared two surgical procedures, PG-TVT (n=44) and TG (n=30), in terms of surgical outcomes, postoperative complications and nutritional status. The Reflux Dise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For patients with early gastric cancer, total and proximal gastrectomy are associated with similar long-term survival [28][29][30] ; however, some studies have indicated that there is a higher rate of anastomosis-related complications in patients who undergo esophagogastrostomy after proximal gastrectomy compared with Roux-en-Y anastomosis after total gastrectomy. [29][30][31][32] In this study, we observed that patients who underwent esophagogastrostomy had a higher rate of leakage compared with those who underwent Roux-en-Y reconstruction (11.83% vs 8.17%, P < 0.05). Therefore, the type of reconstruction is an independent factor associated with the risk of anastomotic leakage.…”
Section: Discussionmentioning
confidence: 61%
“…For patients with early gastric cancer, total and proximal gastrectomy are associated with similar long-term survival [28][29][30] ; however, some studies have indicated that there is a higher rate of anastomosis-related complications in patients who undergo esophagogastrostomy after proximal gastrectomy compared with Roux-en-Y anastomosis after total gastrectomy. [29][30][31][32] In this study, we observed that patients who underwent esophagogastrostomy had a higher rate of leakage compared with those who underwent Roux-en-Y reconstruction (11.83% vs 8.17%, P < 0.05). Therefore, the type of reconstruction is an independent factor associated with the risk of anastomotic leakage.…”
Section: Discussionmentioning
confidence: 61%